PENGARUH NON PERFORMING FINANCING (NPF), CAPITAL ADEQUACY RATIO (CAR), DAN DANA PIHAK KETIGATERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH - Suliati, Suliati; Adji, Koenta; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
The purpose of this study is to examine and explain the effect of Non Performing Financing, CapitalAdequacy Ratio and Third Party Funds on profitability (ROA) registered at the Financial Services Authority(OJK) in 2012-2016. The population of this study is the Islamic People's Financing Bank (BPRS) registeredwith OJK. Sampling using the total sampling method. From a population of 12 Islamic banks, the authors usesecondary data in the form of financial statements. Methods of observation for 5 years (2012-2016). Analysis ofthe data used in this study is the classic assumption test and hypothesis test. While the analytical method used ismultiple linear regression analysis. The results of this study indicate that the Non Performing Financingvariable, Capital Adequacy Ratiodan DPK has no effect on profitability (ROA)